2011
DOI: 10.1037/a0024642
|View full text |Cite
|
Sign up to set email alerts
|

Teaching trauma-focused exposure therapy for PTSD: Critical clinical lessons for novice exposure therapists.

Abstract: Over the past 10 years, our experiences delivering exposure therapy and teaching clinicians to deliver exposure therapy for PTSD have taught us some important lessons. We will focus on lessons learned as we have attended to clinicians’ experiences as they begin to implement and apply the therapy. Specifically, we highlight common therapist expectations including the beliefs that the exposure therapy requires a new set of clinical skills, therapists themselves will experience a high level of distress hearing ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 17 publications
1
26
0
1
Order By: Relevance
“…This suggests that conventional trainings might not suffice to convince clinicians to actually apply exposure in routine clinical practice. Especially in the treatment of PTSD, therapists tend to be concerned regarding utilisation of exposure, for instance, due to the fear of “re‐traumatizing” the patient (Cook, Schnurr, & Foa, ) or due to a feared “over‐engagement” of the patient (Zoellner et al, ). Importantly, as supported by our data, less negative beliefs about exposure consistently predicted the frequent use of therapist‐guided exposure, underlining the importance of addressing these concerns in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that conventional trainings might not suffice to convince clinicians to actually apply exposure in routine clinical practice. Especially in the treatment of PTSD, therapists tend to be concerned regarding utilisation of exposure, for instance, due to the fear of “re‐traumatizing” the patient (Cook, Schnurr, & Foa, ) or due to a feared “over‐engagement” of the patient (Zoellner et al, ). Importantly, as supported by our data, less negative beliefs about exposure consistently predicted the frequent use of therapist‐guided exposure, underlining the importance of addressing these concerns in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Negativna vjerovanja kliničara prepreka su u kompetentnoj primjeni terapije izlaganjem (27,32), usprkos tome što istraživanja potvrđuju da je ona učinkovita, sigurna, izdržljiva i nosi minimalne rizike kad se ispravno primjenjuje. Negativna očekivanja potiču terapeute koji se odluče na njezinu primjenu na pretjerani i nepotrebni oprez, kao što je izbor zadataka koji izazivaju manju anksioznost, prerano prekidanje izlaganja, toleriranje čestog korištenja sigurnosnih ponašanja i strategija za smanjenje anksioznosti, te izbjegavanje izlaganja klijenata najjače zastrašujućoj situaciji (26), što značajno smanjuje učinkovitost tretmana.…”
Section: Introductionunclassified
“…Prisutnost komorbidnog depresivnog poremećaja također se često smatra preprekom za uspješnu primjenu terapije izlaganjem (37). Premda se prisutnost komorbidnog psihotičnog poremećaja ranije smatrala glavnim kriterijem isključivanja za primjenu terapijskih is inherently unethical (28), aversive and unacceptable for the patient (32), and that it increases treatment dropout (33). On the other hand, studies have found no differences in treatment dropout between exposure therapy and other behavioural-cognitive treatments (34).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Learning to be a trauma therapist involves additional challenges related to the implementation of evidence-based practices that involve repeated exposure to the traumatic details of survivors' experiences (Foa, Keane, Friedman, & Cohen, 2009;Zoellner et al, 2011). Faculty researchers have begun to call for research on understanding the effects of such trauma education and training programs on graduate students (Courtois & Gold, 2009;El wood, Mott, Lohr, & Galovski, 2011).…”
mentioning
confidence: 97%